The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1002/ejhf.1433
|View full text |Cite
|
Sign up to set email alerts
|

Cardiorespiratory fitness, body mass index and heart failure incidence

Abstract: Aims Obesity is associated with increased risk of heart failure (HF). This risk may be modulated by improved cardiorespiratory fitness (CRF) as CRF is associated with favourable health outcomes. Thus, we assessed the interaction between body mass index (BMI), CRF and HF. Methods and results Cardiorespiratory fitness and BMI were assessed in 20 254 US male veterans (mean age 58.0 ± 11.3 years), who completed a maximal exercise treadmill test between 1987 and 2017. All had no evidence of ischaemia or HF prior to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
56
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 69 publications
(68 citation statements)
references
References 29 publications
0
56
1
Order By: Relevance
“…The current findings of Kokkinos et al . are very relevant and welcome, as they have several clinical implications for HF prevention.…”
Section: Individual Studies and Meta‐analyses Of Prospective Studies mentioning
confidence: 54%
See 2 more Smart Citations
“…The current findings of Kokkinos et al . are very relevant and welcome, as they have several clinical implications for HF prevention.…”
Section: Individual Studies and Meta‐analyses Of Prospective Studies mentioning
confidence: 54%
“…There is little knowledge on the association and interaction between CRF, BMI, and incident HF. In this context, Kokkinos et al . have conducted an elegant and clinically valuable study that aimed to assess the interactive effect of CRF and BMI on the incidence of HF in US male veterans.…”
Section: Individual Studies and Meta‐analyses Of Prospective Studies mentioning
confidence: 99%
See 1 more Smart Citation
“…Obesity is a condition characterized by an excessive accumulation of fat in adipose tissue; it is linked to an increased risk of chronic diseases, disability, and mortality [1], and is also often associated with poor physical fitness levels, e.g., muscle strength [2], and cardiorespiratory fitness [3]. Moreover, both obesity and physical performance are associated with quality of life.…”
Section: Introductionmentioning
confidence: 99%
“…10 Several reports have also observed that the association of obesity with adverse outcomes is reduced when factored for CRF levels. 11 These observations suggest that the association between obesity and increased CVD risk may reflect low CRF and that adverse consequences of obesity on CVD may be offset by improved levels of CRF. 12 Despite the minefield of evidence on the relationships among physical fitness, obesity, and adverse health outcomes, this interplay is still not well understood and is still debated.…”
mentioning
confidence: 96%